2017
DOI: 10.1371/journal.pone.0171867
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive approach to understand somatic symptoms and their impact on emotional and psychosocial functioning in children

Abstract: IntroductionSomatic symptoms are frequently reported by children with significant impairment in functioning. Despite studies on adult populations that suggest somatic symptoms often co-occur with difficulties in identifying and describing feelings, little research has been done in childhood. This study aimed to investigate the prevalence and frequency of somatic symptoms as well as to investigate the functional impairment in children with high number of self reported somatic symptoms versus those with fewer so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 42 publications
(46 reference statements)
3
34
0
Order By: Relevance
“…Past research across all settings, albeit limited, suggests that the overall burden of SD is large among conflict-affected populations and that SD hinders daily functioning across varying demographics [11,23,24]. A deeper understanding of the scope of this problem would be beneficial to key health system actors during efforts to provide required mental health and psychosocial support (MHPSS) services following humanitarian crises.…”
Section: Introductionmentioning
confidence: 99%
“…Past research across all settings, albeit limited, suggests that the overall burden of SD is large among conflict-affected populations and that SD hinders daily functioning across varying demographics [11,23,24]. A deeper understanding of the scope of this problem would be beneficial to key health system actors during efforts to provide required mental health and psychosocial support (MHPSS) services following humanitarian crises.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that alexithymia is broadly associated with various mental and physical health problems ( Cerutti et al, 2016 , 2017 ; Gatta et al, 2016 ). Individuals with alexithymia are more likely to have a limited ability to adaptively cope with stressful conditions and tend to encompass unhealthy behaviors such as alcohol and drug use ( Lumley et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…The CSI, specifically the short version (CSI-24) [ 17 , 37 ], which was translated into Italian by Cerutti and coworkers [ 21 ] using the translation/back-translation method, was used to assess each child's perception of somatic symptoms (SSD). This instrument is one of the most commonly used to assess somatisation among children and adolescents [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Using this type of assessment, some studies have shown a significant relationship between somatic symptoms (SS) and alexithymia, a psychological factor abundantly investigated in chronic pain [ 19 ] in both adults [ 20 ] children [ 21 ]. Poor emotional awareness and the alexithymia personality trait seem to play an important role in the aetiology of functional somatic complaints featuring pain as a form of somatisation.…”
Section: Introductionmentioning
confidence: 99%